A Study of the Relationship Between Teachers’ Perceptions Towards Reward System and Their Organization Commitment in Shanxi Experimental Secondary School - Li, Xiaotian; Ye, Yan (Scholar: Human Sciences, 2021)
Abstract: The main purpose of this study was to determine the relationship between teachers’ perceptions towards the reward system and their organization commitment in Shanxi experimental secondary school. The study firstly assessed the teachers’ perceptions towards reward system, examined their organization commitment, lastly found the relationship between reward system and organization commitment. The study was conducted to survey of 100 full time teachers from academic year 2019 at Shanxi experimental secondary school. Means and Standard Deviations were used to report the level of teachers' perceptions towards reward system and their organization commitment; to analysis the relationship between these two variables, Pearson Product Moment Correlation Coefficient was applied to test in this paper, the r =.701, Sig.(2-tailed) was .000. The results showed that, the teachers in the target school had a relatively positive attitude towards reward system. The Pearson Correlation test indicated that there was a significant relationship between teachers’ perceptions towards reward system and their organization commitment in Shanxi experimental secondary school, China.